Hawker culture and its infrastructure: Experiences and contestations in everyday life - Kong, Lily (Institutional Knowledge at Singapore Management University, 2023)
Hawker foods characterize urban Asia, with similarities and differences across cities that forge both cultural commonalities and distinctions. From the itinerant to the fixed location, from the temporary sites to the purpose-built, hawker foods are served in informal settings, with varying degrees of tradition and innovation, hygiene and squalidness, local authenticity and globalized influence. In the side-streets of Beijing where local delicacies such as scorpion are served, to the abundant food cart vendors on Bangkok streets, to the warung (small, typically family-owned eateries) in Surabaya, and the carefully planned and designed hawker centres in Singapore, hawker culture is a distinctive characteristic of Asian urban culture. This usually low-priced food option feeds a consumption culture that is casual, relaxed and pervasive. The nature of this consumption culture is forged from multi-layers of infrastructure that enable the (re)production of hawker or street food culture. This infrastructure includes physical, social, economic and digital dimensions, with the relative interplay of the various dimensions resulting in distinctive characteristics of hawker culture in different urban contexts. This chapter refers to physical infrastructure as the sites and locations, architectures, physical structures and systems that enable the production and consumption of hawker foods. These could be purpose-built hawker centres or makeshift street-side stalls. The latter is intuitive, and indeed, embedded in the very meaning of “hawking”, but as this chapter will illustrate, itinerance need not be a requisite physical manifestation, and relative permanence and fixity can also characterize hawkers. Social infrastructure refers to the person of the hawker, the quintessential cook, micro-businessperson, purchaser, marketing and sales personnel, often all rolled in one. Economic infrastructure takes the form of economic policies and business models that enable hawker culture, and digital infrastructure refers to new models of transaction, including e-payments, online ordering and other practices enabled by digital technologies, which have empowered some hawkers while leaving others behind.